The effects of bar model in the students' performance in solving word problems involving fractions - Cancio, Jireh Anne G. (Animo Repository, 2022)
This study was conducted to improve the teaching of multiplication of fractions by introducing the bar model as an alternative to the traditional method in solving word problems involving fractions. Students’ performance in problem solving while using the bar model had been documented and analyzed. The participants of the study were the 24 grade 5 students of a private school in Tarlac City, Tarlac. In this study, the researcher adopted the Plan-Do-Study-Act (PDSA) model for action research and used research instruments such as test questionnaires (pretest and posttest), written interview, and perception survey. Data gathering was conducted initially by asking the students to answer a pretest. Based on the results, their level of proficiency in solving word problems involving fractions and their difficulties with the use of the traditional method were identified. A posttest was administered immediately after the 3 intervention lessons to determine the students’ improvement in their level of proficiency. The students were also asked to respond to interview questions in written form and to share their opinion about the use of the bar model through a perception survey. Based on the data gathered and analyzed, it was found out that the overall level of proficiency of students in problem solving with the use of bar model had improved as well as their levels of proficiency in the stages of problem solving particularly in understanding the problem and planning for solution. Their overall proficiency in problem solving rose from ‘beginning’ to ‘developing’ while their proficiency levels in understanding the problem and planning for solution rose from ‘beginning’ to ‘approaching proficiency’ and from ‘beginning’ to ‘developing’, respectively. The results further revealed that the difference between the pretest and posttest was statistically significant based on the paired t-test analysis. The positive effect of the bar model in the students’ performance was also shown by the increase in the number of problems they solved successfully in the posttest. The percentage of word problems that they were able to solve correctly increased significantly. Furthermore, the findings drawn from this study suggest that bar model may be considered as an effective alternative to traditional method in terms of solving word problems involving multiplication of fractions.